S77 Modulatory effects of rheumatoid arthritis IGG on neutrophil activation: a potential role in RA-ILD. (15th November 2016) - Khawaja, AA; Pericleous, C; Ripoll, VM; Booth, HL; Holmes, V; Mikolasch, T; Giles, I; Porter, JC
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune rheumatic disease (ARD) characterised by circulating autoantibodies, including anti-citrullinated protein antibodies (ACPA). Many RA patients have extra-articular disease, including ∼10% with interstitial lung disease (ILD). Risk factors for RA-ILD include: male sex; age; smoking history and ACPA positivity. Hypothesis: We propose that RA-IgG, including ACPA, modulate neutrophil functions including: generation of reactive oxygen species (ROS), neutrophil adhesion and generation of neutrophil extracellular traps (NETs) that may contribute to joint and extra-articular tissue damage, including ILD. Methods: Neutrophils and IgG were isolated from RA patients or healthy controls (HC). Bronchoalveolar lavage (BAL) was performed on ILD patients and controls underdoing bronchoscopy for other reasons. ROS production was measured using an enzymatic assay to assess hydrogen peroxide (H2O2) generation. Neutrophil integrins were quantified by flow cytometry. Effects of purified IgG upon neutrophil adhesion to immobilised fibrinogen (Mac-1/aMß2-dependent) and fibronectin (VLA-4/a4ß1-dependent) were determined using a fluorescent adhesion assay. NETosis was measured using a novel capture ELISA. Results: We demonstrated increased NETs in the BAL of patients with active ILD (n = 3; ARD-ILD) compared to those with inactive disease (n = 2; IPF and ARD-ILD) or controls (n = 1; CLL). In addition, we showed binding of RA-IgG to control neutrophils, which increased with neutrophil activation. Stimulation of HC (n = 12) and RA (n = 7) neutrophils with PMA produced similar rates of H2O2 generation (p = 0.9939). Exposure of HC neutrophils to RA-IgG (n = 9) however, increased H2O2 production compared to HC-IgG (n = 9) (p < 0.0001), which was not blocked by FcR blockade. RA-IgG also enhanced PMA-stimulated adhesion of HC neutrophils to fibrinogen (p = 0.0028) and fibronectin (p = 0.0024), which was inhibited by aMß2 or ß1 integrin blockade respectively. RA-IgG increased both spontaneous (p = 0.0248) and PMA-induced (p = 0.0200) NETosis of HC neutrophils compared to HC-IgG. Immunofluorescence studies demonstrate that aMß2 activation induces NETosis. Further examination found that NETosis could be suppressed by p38 MAPK inhibition (p = 0.0034). Conclusion: We have shown that RA-IgG modulates several aspects of neutrophil activation and function. In addition, we found increased neutrophil activation in the lungs of patients with active ARD-ILD. Further work is underway to evaluate the contribution of these processes to the pathogenesis of RA-ILD.